THE EFFECT OF TAX PLANNING AND POLITICAL COSTS ON PROFIT MANAGEMENT WITH PROFITABILITY AS MODERATING VARIABLES - Salama, Sri Nofita; Randa, Fransiskus; Ng, Suwandy (Faculty of Economics dan Business, Atma Jaya Makassar University, 2022)
This study aims to investigate whether the tax planning and political cost has an influence on earning management, and whether profitability moderates the influence of tax planning and political cost on earning management. The population on this study is all the companies listed in Indonesia Stock Exchange on 2017- 2019 period. The number of sample are 56 companies each year determined usingthe purposive sampling method. Collecting data used documentation of financial statement from Indonesia Stock Exchange. Data were analyzed using SPSS 21. The result of this study shows that tax planning has a significant and positive impact on earning management, in contrast, the political cost has no impact on earning management. Profitability moderates the relation of tax planning andearning management but doesn’t moderates the impact of political cost and earning management.